Catholics On Call : Discerning a Life of Service in the Church - Ryan, Robin (Book collections on Project MUSE., 2010)
"Hearing God's call and choosing a life of service to the church is one of the most important, and most difficult, decisions that a person can make. The authors of Catholics on Call: Discerning a Life of Service in the Church offer valuable insights into religious life and vocational discernment. This book is a wonderful resource for anyone who is in the process of vocational discernment. It is equally valuable for those who know someone who is considering an ecclesial ministry. A must read." --Book Jacket.